2012
DOI: 10.1016/j.aap.2010.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle riders’ perception of helmet use: Complaints and dissatisfaction

Abstract: Abstract. In accidents which involve two-wheeled vehicles the helmet plays a life-saving role, but very little is known about the motorcycle rider's perceptions of the helmet. We evaluated the relationships between having been involved in an accident and dissatisfaction with the helmet and between the perceptions of the motorcycle riders and the objective features of the helmet. It is a case-control study: riders of motorized two-wheelers who were involved in accidents (cases) were compared with a sample of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Discomfort of the helmet seems to be an important barrier of helmet use in previous research (Khan et al, 2008;Li et al, 2008;Ranney et al, 2010;Skalkidou et al, 1999). Despite that, Orsi et al (2012) found that, even though the majority of riders were dissatisfied with their helmets, complaints did not seem to be associated with the objective features of the helmet. Nevertheless improving helmet comfort in order to increase their level of user satisfaction seems to be important.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Discomfort of the helmet seems to be an important barrier of helmet use in previous research (Khan et al, 2008;Li et al, 2008;Ranney et al, 2010;Skalkidou et al, 1999). Despite that, Orsi et al (2012) found that, even though the majority of riders were dissatisfied with their helmets, complaints did not seem to be associated with the objective features of the helmet. Nevertheless improving helmet comfort in order to increase their level of user satisfaction seems to be important.…”
Section: Discussionmentioning
confidence: 57%
“…A number of environmental factors have also been linked to helmet use such as the road type, the weather and the time of day (Gkritza, 2009;Hung et al, 2006;Li et al, 2008;Nakahara et al, 2005;Skalkidou et al, 1999). Likewise, a number of helmet features have been shown to reduce the likelihood of using a helmet due to causing discomfort or influencing the rider's perception such as noisiness, temperature, poor ventilation, field of vision, functional and design errors (Bogerd, Rossi, & Bruhwiler, 2010;Buyan et al, 2006;Kennedy, Adetifa, Carley, Holt, & Walker, 2011;Mlynski, Kozlowski, & Zera, 2009;Orsi et al, 2012). Riders' beliefs and attitudes towards helmet use have also been shown to affect their helmet use practices with beliefs about injury prevention and safety being among the major facilitators of helmet use and beliefs about physical discomfort and limited vision and hearing, being major barriers of helmet use (Khan et al, 2008;Li et al, 2008;Ranney et al, 2010;Skalkidou et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Evidently, the emotional component plays a critical role in the adoption of this safety measure. As shown in previous studies, negative feelings associated with helmet use (e.g., inconvenience) tended to be an argument put forth by those who do not use a helmet (Orsi et al, 2012;Zamani-Alavijeh et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Perceived limitations on visual and auditory capacities (Papadakaki et al, 2013;Hung et al, 2008;Ranney et al, 2010), subjective reports of helmet weight, and increased temperature when wearing helmets are among the reasons motorcyclists refuse to wear helmets (Li et al, 2008;Orsi et al, 2012). The inconvenience of carrying the helmet when the motocycle is parked is also seen as a deterrent to helmet use.…”
Section: Introductionmentioning
confidence: 95%